Public Relations and Peace Building: A Study of Bayero University Relationship with Host Communities - Louis Benard (Britain International for Academic Research (BIAR) Publisher, 2025)
The aim of this study is to examine public relations and peacebuilding in Bayero University. The objectives of the study are to identify the community relations activities used by Bayero University, Kano in building peace with host communities; to find out if Bayero University, Kano target communities in their community relations programmes for peace building; to find out host communities’ perceptions of the community relations activities adopted in peace building by Bayero University, Kano; and to determine the level of contribution public relations practice has made towards long term peace building by Bayero University, Kano. The study adopted the theoretical tenets of Excellence Theory. Survey method was employed quantitative approach as a method of data collection. A sample size of 400 respondents was selected for the survey method. Cluster sampling was used for the survey method. Questionnaire was used as instrument of data generation for the survey and structured face-to-face in-depth interview was used for qualitative data. While Statistical Package for Social Sciences (SPSS) software was used to analyse the quantitative data. The study discovered that the community relations activities adopted by Bayero University, Kano are through meeting between community and university management. The study found that the community relations programs adopted by Bayero University, Kano help in resolving conflict in the communities. The study concludes that public relations has long been recognised as an important tool for promoting peace by disseminating messages and information that have the power to influence public opinion.